A novel development of optimized hybrid MPPT controller for fuel cell systems with high voltage transformation ratio DC–DC converter - Zaheda Sultana; CH Hussaian Basha; Mohammed Mujahid Irfan; Faisal Alsaif (Scientific Reports)
Abstract The world is moving towards the utilization of hydrogen vehicle technology because its advantages are uniformity in power production, more efficiency, and high durability when compared to fossil fuels. So, in this work, the Proton Exchange Membrane Fuel Stack (PEMFS) device is selected for producing the energy for the hydrogen vehicle. The merits of this fuel technology are the possibility of operating less source temperature, and more suitability for stationery and transportation applications. Also, it provides a high amount of power density for heavy-duty electric vehicle applications. However, the major issue of the fuel stack technology is excessive current generation. Here, in the first objective, a Single Switch Wide Voltage Supply Converter (SSWVSC) is proposed to optimize the current levels of the fuel device thereby reducing the energy conduction losses of the entire system. In the 2nd objective, the duty cycle generation for the converter and handling of nonlinear energy generation of the fuel device has been done by introducing the Greywolf Optimization-dependent Adaptive neuro-fuzzy inference system (ANFIS). The features of this hybridization concept are less iteration number needed, less disturbance in MPP position, low stabilizing time of the fuel module production voltage, and more reliability. Here, the fuel module interfaced DC-DC circuit is studied by utilizing the MATLAB software and the introduced converter is tested only with programmable DC-Source.